PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) DENGAN DUKUNGAN ORGANISASI SEBAGAI VARIABEL MODERATING (Studi Pada Karyawan PT PLN (Persero) APJ Semarang) - Lestari, Prima; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2015)
This study examined the effect of job satisfaction on organizational commitment,the effect of job satisfaction and organizational commitment to direct OCB, the effect of job satisfaction on OCB indirect through organizational commitment as an intervening variable, and the effect of organizational support as moderating variable on the relationship of job satisfaction and OCB at PT PLN (Persero) APJ Semarang. This research used the survey method with three forms of regression analysis, the Linear Regression Analysis, Moderate Regression Analysis (MRA), and Path Analysis. The study was conducted on the employees of PT. PLN (Persero) APJ Semarang. The sampling technique was conducted by using Slovin, so that the samples in this study were 77 employees, representing five divisions in PT. PLN (Persero) APJ Semarang.Regression test results indicate that job satisfaction has positive and significant effect on organizational commitment. Other regression test results indicate that job satisfaction and organizational commitment have positive and significant effect on OCB directly. MRA test results showed that the organization support was able to moderate (strengthening) the relationship between job satisfaction and OCB. MRA test results also indicate the nature of organizational support variable as a pure moderator. Furthermore, test results of Path Analysis showed that job satisfaction can affect OCB indirectly through organizational commitment.